Production and Isolation of Magnetic Protein Crystals in HEK293T Cells - Thomas Li; Bianxiao Cui (Bio-Protocol, 2020)
Advances in protein engineering have enabled the production of self-assembled protein crystals within living cells. Our recent publication demonstrates the production of ftn-PAK4, which is a ferritin-containing crystal that can mineralize iron and become magnetic when isolated. We have developed an optimized protocol for the production and isolation of PAK4-based crystals. The crystals are first grown in low-passage HEK293T cells, released using a lysis buffer containing NP-40 and DNase, and collected under careful centrifugation conditions. Our protocol maximizes the purity and yield of crystals and is quick and straightforward.